(untitled) (Journal of Educational Sciences, 2023)
The area of science known as environmental pedagogy defines methodological approaches to environmental education. Environmental education has the task of understanding the phenomena of the environment and improving the ecological culture of students. Environmental pedagogy is particularly pertinent in the context of changing educational paradigms. In light of globalization, we think it is crucial to take current environmental pedagogic problems into account in contemporary study. The primary objective of this article is to systematize the opinions of international scientists on this issue. Therefore, this research paper does not pay attention to scientific literature written in Kazakh and Russian. In foreign studies, the concepts of «Environmental Pedagogy», «Ecological Pedagogy» and «Ecopedagogy» are used to interpret environmental pedagogy. In this study, «Environmental Pedagogy» was taken as the main keyword, and to solve the main task, a qualitative content analysis of articles indexed in the Scopus database was carried out. The author was able to obtain the results of the study by analyzing 31 articles. The thematic scale of the problem determined three themes for the research work. Themes included the problems of environmental pedagogy in secondary and higher education, its focus on social problems, and definitions of environmental justice. The article gives the author’s definition of the concept of environmental pedagogy based on modern research. Key words: environmental pedagogy, environmental education, natural environment, curriculum, environmental justice.